PEMBERIAN SUSU KEDELAI TERHADAP AMENOREA SEKUNDER PADA REMAJA PUTRI KELAS 7 TAHUN 2022 - Hasvita Hasvita; Novi Pasiriani; Arsyawina Arsyawina (Politeknik Kesehatan Kementerian Kesehatan Kalimantan Timur, 2022)
Abstract One of the menstrual cycle problems that occurs in young women is secondary amenorrhea. The purpose of this study was to determine the effect of giving soy milk to changes in secondary amenorrhea in female adolescents. This type of research is an experimental study with a nonequivalent control group design. Sampling using purposive sampling technique. The sample of this study was 20 grade 7 girls at Madrasah Tsanawiyah at the Babussalam Tanah Grogot Islamic Boarding School who experienced secondary amenorrhea. Data were analyzed using the Wilcoxon test. Based on the Wilcoxon test, the p value was 0.008 (p <0.05) so that there was an effect of giving soy milk on secondary amenorrhoea in female adolescents. There is an effect of giving soy milk to secondary amenorrhoea in grade 7 girls at Madrasah Tsanawiyah at Babussalam Tanah Grogot Islamic Boarding School. Keywords: Secondary Amenorrhea, Soy Milk, Young Women Abstrak Salah satu masalah siklus menstruasi yang terjadi pada remaja puti adalah Amenore sekunder. Tujuan penelitian ini untuk mengetahui pengaruh pemberian susu kedelai terhadap perubahan amenore sekunder pada remaja putri. Jenis penelitian studi eksperimental dengan rancangan nonequivalent control group design. Pengambilan sampel menggunakan teknik purposive sampling. Sampel penelitian ini remaja putri kelas 7 Madrasah Tsanawiyah di Ponpes Babussalam Tanah Grogot yang mengalami Amenore sekunder, berjumlah 20 orang. Data dianalisis menggunakan uji Wilcoxon. Berdasarkan uji Wilcoxon didapatkan p value 0,008 (p<0,05) sehingga terdapat pengaruh pemberian susu kedelai terhadap amenorea sekunder pada remaja putri. Ada pengaruh pemberian susu kedelai terhadap amenorea sekunder pada remaja putri kelas 7 Madrasah Tsanawiyah di Ponpes Babussalam Tanah Grogot. Kata Kunci : Amenorea Sekunder, Susu Kedelai, Remaja Putri